FAULT-RELATED METAMORPHISM AND ASSOCIATED GOLD MINERALIZATION FOLD SYSTEMS, AS ILLUSTRATED BY THE SOUTHERN URALS - Rudskiy V.G. (My University, 1990)
Fault-related metamorphism is one of the types of dynamic metamorphism whose allochemical crystalloblastic processes develop in deep fault zones under considerable dynamic load and involve gas-liquid fluids. The proposed model of fault-related metamorphism is the result of work done by us in the Kumak gold deposit in the central ore-bearing part of the Kumak-Kotansinskaya warped zone, a fragment of the regional geosuture called the Chelyabinsk-Taldyk deep fault. This ore deposit, whose geologic structure was analyzed by us earlier, is in the narrowest part of the meridionally extending Anikhovskiy graben-synclinorium that separates the Adamovskiy and the Tekel'dytau horst-anticlinoria, or polymetamorphic complexes (PMC).